Pengaruh Kelengkapan Produk Dan Harga Terhadap Pembelian Ulang Konsumen (Studi Kasus Freshmart Bahu Manado) - Enos Korowa; Sontje Sumayku; Sandra Asaloei (JURNAL ADMINISTRASI BISNIS, 2018)
Marketing practices are constantly being upgraded and updated to improve the chances of success for a company. Good marketing canâ€™t be separated from the level of products and prices offered to consumers, products are varied and affordable prices will provide a distinct advantage for companies engaged in the field of trade because this will provide a boost to consumers to take a repeat action in the company. This study aims to determine whether the effect of completeness of products and prices on the repurchase of consumers at Freshmart Bahu Manado. The method used is quantitative research method, by taking sample members as much as 60 respondents by using multiple regression analysis. The results showed that there is a significant influence on the level of product and price to consumer buyback seen from the results of multiple regression tests and correlation coefficient test results. So the hypothesis states there exists the effect of product and price on consumer buyback is acceptable. with the conclusion that the better the quality of the product and the price offered will be the higher level of repurchase of the consumer, as well as the lower the product and the price offered, the lower the repurchase rate of the consumer.Â Keywords: Products, Price and Consumer Buyback